Acute effects of fresh versus dried Hayward green kiwifruit on sleep quality, mood, and sleep-related urinary metabolites in healthy young men with good and poor sleep quality - Kanon, Alexander P.; Giezenaar, Caroline; Roy, Nicole C.; McNabb, Warren C.; Henare, Sharon J. (Frontiers in Nutrition, 2023)
Background & aims: Daily kiwifruit (KF) consumption has been associated with improved sleep quality, but underlying physiological mechanisms are unknown. This study examined acute effects of fresh and dried green KF, compared with a water control, on sleep quality, mood, and urinary serotonin and melatonin metabolite concentrations. Methods: 24 men (age: 29±1 yrs, body mass index: 24±1 kg/m2) with poor (n=12) or good (n=12) sleep quality participated in a randomized, single-blind crossover study. One of three treatments was consumed with a standardized evening meal; 1) the flesh of two fresh green KF; 2) dried green KF powder (including skin; equivalent to dry matter of two fresh KF) mixed with water; or 3) a water control, in their own home. Subjective and objective sleep quality, mood, waking urinary 5-hydroxyindoleacetic acid (5-HIAA), 6-sulfatoxymelatonin (aMT6s), vitamin C and B-vitamin concentrations were determined. Results: Regardless of sleep quality group, compared to control, morning sleepiness, alertness upon awakening, and vigor were improved (p<0.05) after dried KF consumption. Compared to control, both fresh and dried KF treatments tended (p < 0.1) toward improved esteem and total mood disturbance. Both KF treatments increased (fresh +1.56±0.4ng/g, p=0.001; dried: +1.30±0.4 ng/g, p=0.004) urinary concentration of the serotonin metabolite 5-HIAA compared to the control (4.32±0.4 ng/g). In poor sleepers, ease of awakening improved by 24% after dried KF consumption (p=0.005) and tended to improve by 13% after fresh KF intake (p=0.052) compared to the control. Good sleepers tended towards 9% improved ratings of getting to sleep with fresh KF (p=0.053) compared to the control. Poor sleepers had lower amounts of some B-vitamins compared to good sleepers (p<0.05). Conclusion: Consumption of dried or fresh KF with a standard evening meal, was associated with improved aspects of sleep quality and mood, possibly mediated through changes in serotonin metabolism. Registration: This trial was registered at www.anzctr.org.au as ACTRN12621000046808.